2021
DOI: 10.1177/01945998211021011
|View full text |Cite
|
Sign up to set email alerts
|

Do Federal Regulations Affect Gender, Racial, and Ethnic Disparities in Chronic Rhinosinusitis Research?

Abstract: Objective The Food and Drug Administration and the National Institutes of Health (NIH) have asserted that diverse demographic representation in clinical trials is essential. In light of these federal guidelines, the objective of this study is to assess the racial, ethnic, and gender demographics of patients enrolled in clinical trials registered with the NIH that evaluate chronic rhinosinusitis with nasal polyposis (CRSwNP) relative to the demographics of the US population. Study Design Cross-sectional study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…A systematic review of prospective chronic rhinosinusitis (CRS) studies in the United States, encompassing over 12,000 patients, demonstrated that every demographic and ethnic minority was significantly underrepresented relative to its portion of the population (and probably relative to its share of CRS patients) 5 . Separate analyses of prospective clinical trials studying CRS and rhinitis through the National Institute of Health and the US Food and Drug Administration have also found that women and minorities are routinely underrepresented 6–8 . It is not hard to imagine a scenario where insurance companies utilize input from these biased data sets to create an algorithm to determine risk of disease progression, for example, and disproportionately deny sinus surgery coverage for women or minorities based on a skewed interpretation of responses to nonsurgical therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of prospective chronic rhinosinusitis (CRS) studies in the United States, encompassing over 12,000 patients, demonstrated that every demographic and ethnic minority was significantly underrepresented relative to its portion of the population (and probably relative to its share of CRS patients) 5 . Separate analyses of prospective clinical trials studying CRS and rhinitis through the National Institute of Health and the US Food and Drug Administration have also found that women and minorities are routinely underrepresented 6–8 . It is not hard to imagine a scenario where insurance companies utilize input from these biased data sets to create an algorithm to determine risk of disease progression, for example, and disproportionately deny sinus surgery coverage for women or minorities based on a skewed interpretation of responses to nonsurgical therapy.…”
mentioning
confidence: 99%
“…5 Separate analyses of prospective clinical trials studying CRS and rhinitis through the National Institute of Health and the US Food and Drug Administration have also found that women and minorities are routinely underrepresented. [6][7][8] It is not hard to imagine a scenario where insurance companies utilize input from these biased data sets to create an algorithm to determine risk of disease progression, for example, and disproportionately deny sinus surgery coverage for women or minorities based on a skewed interpretation of responses to nonsurgical therapy.…”
mentioning
confidence: 99%